Evaluation of aesthetic and mechanical properties of single shade dental polymer resin: an in vitro study - Lim, Chien Wen; Kelkar Kasturi Chandrashekhar; Noor Azlin Yahya; Hadijah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study evaluated the aesthetic and mechanical properties of single shade resin composite comparing with three different resin composites. Colour matching was performed on ninety class III preparations on acrylic central incisors with shades B1, B2, and A3. One single shade (Omnichroma) and three different multishade resin composite (Filtek Universal Restorative; Palfique LX5; Beautifil II) were used for restoration on each side. Digital photograph was taken under standardized set-up. Colour measurements were taken in the centre of restoration, and tooth surface 1.0 mm from the tooth/restoration margin. The colour difference was analysed using CIELAB equation. For colour stability and surface roughness evaluation, resin composites (10 × 2 mm) were prepared and polished with Sof-LexTM discs. Baseline colour and surface roughness were assessed using digital spectrophotometer and 3D Optical Surface Texture Analyzer, respectively. After 28 days of immersion in distilled water or coffee, post soaking colour changes and surface roughness were recorded. Flexural strength test was performed on 40 specimens (25 × 2 × 2 mm) according to ISO 4049. Three point bending test was performed using the universal testing machine. Omnichroma showed higher colour difference compared to composites in B1 shade (p<0.05). After 28 days of coffee immersion, Omnichroma had significantly different colour stability compared to multi-shade system (p<0.05). There was no difference between the surface roughness of Omnichroma with multi-shade system. Omichroma exhibited the highest flexural strength statically. Further strengthening is needed to enhance Omnichroma’s properties for clinical use while preserving its ability to match surrounding tooth structure.